Assessment of Length of Maternal Cervix between 18 and 24 weeks of Gestation in a Low-Risk Brazilian Population - Andrade, Soraya Gomes de Amorim; Andrade, Fernando Moreira de; Araujo Júnior, Edward; Pires, Cláudio Rodrigues; Mattar, Rosiane; Moron, Antonio Fernandes (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Purpose To determine cervical biometry in pregnant women between 18 and 24 weeks of gestation and the ideal mode of measurement of cervical length in cases of curved and straight cervical morphology.Methods The uterine cervices of 752 low-risk pregnant women were assessed using transvaginal ultrasound in a prospective cross-sectional study. In women with straight uterine cervices, cervical biometry was performed in a continuous manner. In women with curved uterine cervices, the biometry was performed using both the continuous and segmented techniques (in segments joining the cervical os). Polynomial regression models were created to assess the correlation between the cervical length and gestational age. The paired Student t-test was used to compare measuring techniques.Results The cervical biometry results did not vary significantly with the gestational age and were best represented by linear regression (R2 = 0.0075 with the continuous technique, and R2 = 0.0017 with the segmented technique). Up to the 21st week of gestation, there was a predominance of curved uterine cervix morphology (58.9%), whereas the straight morphology predominated after this gestational age (54.2%). There was a significant difference between the continuous and the segmented measuring methods in all the assessed gestational ages (p < 0.001).Conclusion Cervical biometry in pregnant women between 18 and 24 weeks was represented by a linear regression, independently of the measuring mode. The ideal measuring technique was the transvaginal ultrasound performed at a gestational age ≥21 weeks.
Keywords: gestation; uterine cervix; biometry; morphology; transvaginal ultrasound